Edukasi Perilaku Hidup Bersih dan Sehat dalam Pencegahan Komplikasi Luka Diabetes Mellitus di Dusun Panggungan Trihanggo Gamping Sleman - Noamperani, Sapta Rahayu; Sukmana, Dhika Juliana; Anggraeni, Fitri Putri; Rini, Sulis Tia; Milataki, Khirniq Qiqi; Apriliani, Elfrida (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Background: Diabetes mellitus (DM) is one of the main challenges in global health with a high incidence rate, including in Indonesia. In Yogyakarta, the diabetes prevalence rate reaches 3,6%, with a significant number of patients experiencing serious complications such as diabetic wounds that can lead to amputations. Purpose: This study aims to expand the public’s knowledge and awareness of clean and healthy living behaviors (PHBS) as an effort to prevent wound complications in diabetes mellitus patients. The community service activity was conducted in Dusun Panggunan Trihanggo, Gamping, involving 25 elderly participants. Methods: The method applied includes outreach in the form of lectures and interactive discussions through question and answer sessions, supplemented by pre-test and post-test to assess the improvement in participants knowledge, with a p-value of 0,03 (p <0,05). The participants enthusiasm was reflected in the numerous questions asked during the Q&A sessions. Conclusion : Education about PHBS has a significancy positive impact on the community of diabetes mellitus patients, enhancing their understanding of the importance of maintaining cleanliness to prevent wound complications. This activity demonstrates that health education is effective in raising awareness and knowledge among the community regarding the health issues they face.